2009
DOI: 10.1016/j.visres.2009.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Binocular properties of curvature-encoding mechanisms revealed through two shape after-effects

Abstract: We investigated the binocular properties of curvature-encoding mechanisms using the shape-frequency and shape-amplitude after-effects (or SFAE and SAAE). The SFAE and SAAE refer to the shifts observed in, respectively, the shape-frequency and shape-amplitude of a sinusoidal test contour following adaptation to a contour with different shape-frequency/shape-amplitude. We examined (i) the contribution of monocular versus binocular mechanisms to the SFAE and SAAE by measuring the interocular transfer of these aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 79 publications
3
17
1
Order By: Relevance
“…Because of variations in the overall magnitude of the shape-frequency aftereffects across subjects, the data for each subject has been normalized to the C/C condition. The experimental protocol was identical to that described in Gheorghiu and Kingdom (2012b), and the data replicate both the earlier findings of Kingdom and Prins (2005) using continuous contours, as well as data from various subsets of these four conditions reported in previous studies, for example the studies that investigated the spatial (Gheorghiu & Kingdom, 2012b), binocular (Gheorghiu et al, 2009b), chromatic (Gheorghiu & Kingdom, 2012a) and motion (Gheorghiu & Kingdom, 2012c properties of surround suppression.…”
Section: Experimental Evidence For De-texturizationsupporting
confidence: 68%
See 2 more Smart Citations
“…Because of variations in the overall magnitude of the shape-frequency aftereffects across subjects, the data for each subject has been normalized to the C/C condition. The experimental protocol was identical to that described in Gheorghiu and Kingdom (2012b), and the data replicate both the earlier findings of Kingdom and Prins (2005) using continuous contours, as well as data from various subsets of these four conditions reported in previous studies, for example the studies that investigated the spatial (Gheorghiu & Kingdom, 2012b), binocular (Gheorghiu et al, 2009b), chromatic (Gheorghiu & Kingdom, 2012a) and motion (Gheorghiu & Kingdom, 2012c properties of surround suppression.…”
Section: Experimental Evidence For De-texturizationsupporting
confidence: 68%
“…Besides local orientation, texture-surround suppression is selective for stereoscopic-depth (Gheorghiu et al, 2009b), and both global motion direction and temporal frequency (Gheorghiu & Kingdom, 2012c. However it is only weakly selective to color direction, and when the central adaptor contour and test are both achromatic, the magnitude of suppression is agnostic to the particular color of the surround (Gheorghiu & Kingdom, 2012a).…”
Section: Tuning Of Surround Suppressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kingdom and Prins (2009) hypothesized that neurons exhibiting iso-orientation surround suppression feed their responses into contour-shape-coding neurons located in higher visual areas, with the functional role of isoorientation surround suppression being to separate isolated contours for the purpose of contour shape encoding. Although computational models suggest that contours that are orthogonally-oriented with their surrounds are enhanced by cross-orientation facilitation (Huang et al, 2008), none of our studies of TSSCS (Gheorghiu et al, 2009a;Gheorghiu et al, 2009b;Kingdom & Prins, 2009) have found evidence for facilitation.…”
Section: Introductioncontrasting
confidence: 65%
“…The importance of TSSCS is that it is the first expression of the effect of a texture surround on the encoding of the shape of a fully visible contour. Although subsequent studies have explored the selectivity of TSSCS to attributes such as stereoscopicdepth, color, and motion (Gheorghiu, Kingdom, & Varshney, 2009a;Gheorghiu, Kingdom, Thai, & Sampasivam, 2009b;, we still know very little about how TSSCS operates and over what spatial extent. In this communication we address these issues.…”
Section: Introductionmentioning
confidence: 99%